COVID-19: opinions and behavior of Italian general population during the first epidemic phase - Genovese, Cristina; La Fauci, Vincenza; Di Pietro, Angela; Trimarchi, Giuseppe; Odone, Anna; Casuccio, Alessandra; Costantino, Claudio; Restivo, Vincenzo; Fantini, Mariapia; Gori, Davide; Azara, Antonio; Deiana, Giovanna; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: On January 9, 2020, the World Health Organization (WHO) declared that Chinese health authorities had identified a new coronavirus strain never before isolated in humans, the 2019-nCoV later redefined SARS-CoV-2, that still today represent a public health problem. The present survey started on 10 February 2020 with the aim of a) assessing the risk perception in healthcare workers and young students, following the evolution of attitudes, perception and knowledge over time, b) provide useful information to the general population during survey.Results: A study sample consisting of 4116 Italian individuals of both sexes was enrolled. High levels of risk perception, low perception of self-efficacy and low levels of knowledge scores (24.55 ± 5.76 SD) were obtained indicating the need for continuous population monitoring as well as further communication strategies carried out at institution levels.Conclusion: The results of the present study could help public health authorities in carrying out informative campaigns for general population and could be an important tool in evaluating public knowledge and misperceptions during the management of the COVID-19. (www.actabiomedica.it)